SEBARAN SITUS MEGALITIK BONDOWOSO: TIPE DAN KARAKTERISTIKNYA - Bagyo Prasetyo (AMERTA, 2009)
Distribution of Megalithic Sites in Bondowoso: Type and Its Characteristic. Result of archaeological research in Bondowoso area indicate a number of 801 megaliths which are grouped into 8 types concerning cylindrical stones, sarcophagi, dolmen, stone mortar, stone chamber, statue, menhir, and stone seat. After being studied using nearest-neighbor analysis, they simply show the existence of 26 megalithic sites distinguished by clustered pattern. Analysis of sites and type of megalith yield 3 groups based on variance of type megalith that is group of sites by low character, medium character, and high character. The empiric data indicate that 73% of sites predominated by a group of low variance character, which indicated that there are less complex activities. Even though, some sites also show character with more possible complexes are place for doing activities oflarger one in a group of broader communities. Keywords: Bondowoso, Megalithic, Interaction, Characteristic